Online English Club for High School Students: Going Globa - Adaninggar Septi Subekti; Andreas Winardi; Arida Susyetina; Fransisca Endang Lestariningsih (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The community service programme was conducted in the form of an English Club intended for high school students. The high school partner was SMA Immanuel Kalasan, Sleman, Yogyakarta Special Regency. A total of 13 students participated in this extracurricular activity. There were six online, synchronous meetings conducted once a week. Themed